Pengaruh Kualitas Pelayanan, Fasilitas dan Persepsi Harga Terhadap Kepuasan Konsumen - Prasetyo, Muslih Dwi; Susanto, Susanto; Maharani, Bernadetta Diansepti (Jurnal Ilmiah Manajemen Kesatuan, 2021)
This study aims to see the effect of service quality, facilities and price perception on customer satisfaction in Yogyakarta Pojur Barbershop customers. This type of research used in this research is descriptive quantitative. The population used in this study were 155 respondents. The sample in this study were 155 customers who had used barbershop pojur at least once. The sampling technique used was nonprobability sampling with data collection methods using a questionnaire. The data analysis technique in this study used multiple linear regression. Based on the results of this study, service quality, facilities and price perceptions simultaneously have a positive and significant effect on customer satisfaction, Service quality has a positive and significant effect on customer satisfaction, facilities have a positive and significant effect on customer satisfaction and price perception is positive and significant towards consumer satisfaction.